A robust and lubricating synergic polymer composite for bionic articular cartilage in the load-bearing region - Wenjie Ruan; Hai Xu; Zejian He; Yu Tong; Qiong Zhang; Qing Bi; Tianhui Ren; Jiao Wang (Materials & Design)
The worldwide ageing of the population and inappropriate exercise lead to damage and wear and tear of articular cartilage in the load-bearing region. This tissue is difficult to regenerate. Therefore, finding a superior biomaterial to replace or substitute the natural cartilage is essential, as it can significantly reduce the risks and pain associated with joint replacement surgery. Herein, we report a novel polymeric material (PU-EP) to achieve synergy of flexibility and rigidity and use it as a medical material to replace natural articular cartilage. This approach skillfully joins the polyurethane and epoxy resin segments, giving the novel polymer network strong mechanical properties and toughness. In addition, the presence of Fe3O4 nanoparticles causes a rolling effect in the composite network PU-EP@NPs under friction, which changes the sliding friction at the friction interface to rolling friction, thus significantly enhancing the lubricity of the network. We believe that this novel polymer network with lubrication function is the most promising material for a class of materials to treat cartilage damage diseases effectively.